Cryptococcal osteomyelitis of the skull in a liver transplant patient. Issue 6 (20th October 2016) - Pudipeddi, Aviv V.; Liu, Ken; Watson, Geoffrey F.; Davis, Rebecca J.; Strasser, Simone I.
Abstract: Cryptococcus neoformans is an opportunistic fungal pathogen and an important cause of morbidity and mortality in immunocompromised patients. We report a case of osteomyelitis caused by C. neoformans in a liver transplant recipient who presented with a headache and scalp lump after sustaining mild head trauma. There was no evidence of central nervous system involvement or dissemination. This is the first known case report of isolated cryptococcal osteomyelitis in a liver transplant recipient.